Применение метода навязывания фазы в псевдокогерентной доплеровскиой РЛС вертикального зондирования - Шевченко, Р. А. (ХНУРЭ, 2012)
Development of methods forming and processing signals in dopier radiolocating stations of vertical probe. The given work is devoted to the modem developments in the field of digital and analog way of signal quasicoherent processing.